Ethylene Carbonate‐Free Electrolytes for Stable, Safer High‐Nickel Lithium‐Ion Batteries. Issue 19 (24th March 2022) - Pan, Ruijun; Cui, Zehao; Yi, Michael; Xie, Qiang; Manthiram, Arumugam
Abstract: Ethylene carbonate (EC) is an important component in state‐of‐the‐art electrolytes for lithium‐ion batteries (LIBs). However, EC is highly susceptible to oxidation on the surface of high‐nickel layered oxide cathodes, making it undesirable for next‐generation high‐energy‐density LIBs. In this study, a simple, yet effective, EC‐free electrolyte (20F1.5M‐1TDI) is presented by adding 20 wt% fluoroethylene carbonate (FEC) and 1 wt% lithium 4, 5‐dicyano‐2‐(trifluoromethyl)imidazole (LiTDI) into 1.5 m LiPF6 in an ethyl methyl carbonate (EMC) electrolyte. The 20F1.5M‐1TDI electrolyte is found to efficiently passivate the graphite anode and stabilize high‐nickel cathodes by a synergistic decomposition of FEC and LiTDI. The LiNi0.9 Mn0.05 Al0.05 O2 (NMA90)/graphite full cell with the 20F1.5M‐1TDI electrolyte, therefore, exhibits an enhanced cycling stability and a suppressed voltage hysteresis growth compared to that with an EC‐containing baseline electrolyte (1 m LiPF6 in EC:EMC, 3:7 in weight, with 2 wt% vinyl carbonate). Advanced analytical tools, such as time‐of‐flight secondary ion mass spectrometry and X‐ray photoelectron spectroscopy, are employed to understand the underlying working mechanism of the EC‐free electrolyte. The present study clearly showcases the great potential of EC‐free electrolytes as a straightforward, practical approach for LIBs with high‐nickel cathodes. Abstract : An ethylene carbonate‐free electrolyte displays long cycle life and improved safety with high‐nickel cathodes in lithium‐ion batteries (LIBs) due to good compatibility with the cathode and graphite anode. With advanced analytical techniques, the working mechanism of the new electrolyte is revealed, which can also help with the design of future electrolytes for high‐nickel LIBs.